Employee Job Satisfaction and Business Performance: The Mediating Role of Organizational Commitment. Issue 2 (June 2021) - Ahmad, Mir Rouf; Raja, Rameez
Purpose: The aim of this research article is to scrutinize the influence of employee job satisfaction on organizational commitment and business performance in the context of retail banking sector in northern India. Design/methodology/approach: A research design of quantitative in nature was used via a structured questionnaire on a sample of 440 Indian commercial bank employees. Research hypotheses were tested by using the structural equation modelling (SEM) technique to evaluate and test the proposed model. Findings: The result of the present study confirms that all facets of job satisfaction affect the satisfaction of employees significantly and, thus, influence the employee's organizational commitment and business performance, respectively. The significance of the indirect path of employee job satisfaction on business performance through organizational commitment has also been tested with the Sobel test, which exhibited significant results. Research implications: This study provides insight into the influence of employee job satisfaction on the organizational commitment and business performance in the Indian commercial banking context in particular, which could benefit management and policymakers as well as other enterprises operating in the same segment. The results suggest that employee job satisfaction strongly contributes to employees' organizational commitment and business performance. Therefore, organizations require that their employees must be contented and pleased with what they do. Originality/value: This research study contributes one more brick to the existing body of knowledge by investigating the casual relation of employee job satisfaction, and organizational commitment as a mediator with business performance, as these causal relations with business performance are very scarce in the context of commercial banking context. Research limitations: This research survey was restricted to commercial banks operating only in northern India. Thus, it limits the generalizability of the results for the context specified only.